A descriptive study of Community Health Evangelism as a model for integral mission - Jason Paltzer; Keyanna Taylor; Janak Patel (Health for All Nations, 2022)
Background: Integral mission health models are often employed by faith-based organizations to address social, physical, and spiritual wellbeing. Given the use of these models like Community Health Evangelism (CHE), the evidence regarding their effectiveness in practice is limited. The purpose of this descriptive study was to identify variation in the initiation, development, implementation, and impacts of Community Health Evangelism as reported by organization members of the Global CHE Network. Methods: A digital survey in English, Spanish, and French was sent via email to Global CHE network members resulting in 27 complete organizational responses for analysis. Survey questions ranged from qualitative open-ended questions to categorial and ranking type questions. Descriptive statistics and inductive thematic analytical methods were used to describe the data. Data were summarized according to organizational size to better understand this influence on the practice of CHE. Responses represent organizations in Africa, Asia, North/Central America, and Europe. Results: The community selection process, committee and CHE volunteer selection criteria, the function of the community champion, time to CHE volunteer home visitation, and achievement of key impacts were some of the areas that showed variation. Measured impacts included understanding of integral mission, use of LePSA(S) as a teaching strategy, multiplication, and community ownership. Discussion: The study aimed to understand the implementation of CHE in the field and identify areas of variation and adaptation that could lead to opportunities or barriers in achieving the desired impacts of CHE. The results show variation in each of the four phases and provide a starting point to further study CHE as an integral mission model. The paper suggests additional opportunities for future research to identify core components that could strengthen and improve the effectiveness and practice of integral mission models.